2013
DOI: 10.3126/njh.v8i1.8328
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Cardiovascular Disease in suburban population of 3 municipalities in Nepal

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…In a study done among the sedentary workers in an Indian city, the major risk factors for CHD were elevated triglycerides, hypertension, and high levels of serum total cholesterol (45). The probable reason for such results is because of the sedentary lifestyle and higher prevalence of central obesity among them (42). These findings point that although WHO/ISH risk charts are a handy and simple tool for CVD risk prediction, but may underestimate the CVD risk burden.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a study done among the sedentary workers in an Indian city, the major risk factors for CHD were elevated triglycerides, hypertension, and high levels of serum total cholesterol (45). The probable reason for such results is because of the sedentary lifestyle and higher prevalence of central obesity among them (42). These findings point that although WHO/ISH risk charts are a handy and simple tool for CVD risk prediction, but may underestimate the CVD risk burden.…”
Section: Discussionmentioning
confidence: 97%
“…Various studies have revealed a variable level of prevalence of CVD risk using the similar WHO/ISH risk prediction charts in some of the Asian countries (viz. China 1.1%, Iran 1.7%, Sri Lanka 2.2%, Nepal 9.8%, and Pakistan 10.0%) (41,42). A combination of three criteria of a chart, high blood pressure and high serum cholesterol; 10.2% subject had a moderate or high risk of CVD event.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies across the world have utilized the WHO/ISH cardiovascular risk prediction charts to estimate the risk in heterogeneous settings. [ 14 37 38 ] In contrast, findings of a study reflected that the WHO/ISH charts were incorrect to discriminate the risk in Malaysian population. [ 39 ] The WHO has recommended that in low-resource settings, measures like individual counseling should be made available based on the extent of cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…However, a variable risk percentage ranging from 1.1% in China to 21.5% in Malaysia has also been observed. [ 15 37 38 ] Realizing the scope and their utility in varied settings, these risk prediction charts are acknowledged as one of the predominant tools to achieve the target 8 (viz. at least 50% of eligible people receive drug therapy and counselling (including glycaemic control) to prevent heart attacks and strokes), under the NCD action plan.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated by using the formula for estimation of proportion for one sample situation. To detect prevalence of 9.5% of moderate and high CVD risk population, as determined by a study conducted in sub-urban municipalities of Nepal [ 20 ], the minimum sample size required was 292 with allowable error of 4% and a design effect of 1.5. Taking into consideration a non-response rate of 15%, we decided to select 343 subjects from all male and female population aged 40–80 years (N = 3712).…”
Section: Methodsmentioning
confidence: 99%